O-181 The predictive value of the menstrual cycle pattern in adolescence on fertility and general health at age 40 years. (30th June 2022) - Van Hooff, M; Caanen, M; Peters, H; Lambalk, C.B
Abstract: Study question: What is the predictive value of the menstrual cycle pattern in adolescence on fertility, cardiovascular- and metabolic health at age 40 years Summary answer: Adolescents with oligomenorrhea are more often treated to conceive, but, are as likely to have children as those with regular menstrual cycles.   What is known already: Polycystic ovary syndrome(PCOS) is the main endocrine disorder in women of reproductive age. Adolescents with oligomenorrhea have a high risk for PCOS and potential subfertility due to ovulatory disorders.  PCOS is also associated with pregnancy complications as pregnancy induced hypertension, pre-eclampsia and gestational diabetes. Furthermore PCOS is related to long-term health risks such as cardiovascular disease and diabetes.  Studies on longitudinal implications of adolescent oligomenorrhea for fertility are lacking. Data on long-term health consequences of PCOS usually  describe the development of these diseases in adult PCOS patients and lack longitudinal input starting at adolescence.   Study design, size, duration: This is a long-term follow-up study based on a unique adolescent study on menstrual irregularities performed between 1990-1997, the Pubertal onset of Menstrual Cycle abnormalities, a prospective  study, the POMP study. We contacted stratified samples of this studycohort two decades after the initial study for a questionnaire assessing PCOS features, fertility history, pregnancy outcome, metabolic and  cardiovascular health.  Participants/materials, setting, methods: 160 of 271 of the invited adult participants completed the questionnaire; the mean adolescent age was 15.3 years and the women were 39.6 years at time of follow-up. 92 had a  regular menstrual cycle as adolescent  and also as adult (REGREG); 15 changed to oligomenorrhea in adulthood (REGOL); 21 oligoamenorrheic adolescents  remained oligomenorrheic (OLOL), and  31 oligomenorrheic girls  developed a regular menstrual cycle pattern (OLREG). Main results and the role of chance: Of those with adolescent regular menstrual cycles(REGREG+REGOL) 12 never tried to conceive,   4 tried but never conceived and 92 of 96(95, 8%) conceived, 89 of 96(92, 7%) delivered at least one living child. The mean time to pregnancy (TTP) in the REGREG subgroup was 7.2(SD 11.2) months  with 14.6% subfertility (TTP > 12 months) compared to a TTP of 14.9 (SD 19.5) months with 35.7% subfertility in the REGOLsubgroup.  47 of 52 adolescents with oligomenorrhea (OLOL+OLREG)  tried to conceive and 45(95, 6%) succeeded to have at least one full term pregnancy. The mean TTP was 12.8 months (SD 19.8)  in the OLOL subgroup versus 13.6 (SD 18.2) months in the OLREG subgoup, respectively 30 % and 24 % had  a TTP > 12 months (p = 0.17). The median number of children was two in all subgroups. The OLOL subgroup had more fertility treatments -40%- than the other subgroups (14-22%) (p = 0.08).  BMI did not differ between the four subgroups. The risk for pregnancy induced hypertension or pre-eclampsia was comparable among all subgroups (14-20%). Gestational diabetes developed in 3 participants all part of the OLOLsubgroup. Adult diabetes (0-5%), hypertension(3-10%), hypercholesterolaemia(0-5%)  were diagnosed most frequently in the OLOLsubgroup, Cardiovascular disease(0-1%) in the REGREG subgroup Limitations, reasons for caution: The numbers in the study are small. However the small difference between the percentage with a least one living child of those with adolescent oligomenorhea versus those with adolescent regular menstrual cycles is reassuring. Time to pregnancy data may have been  biased by early treatment of oligomenorrheic adults. Wider implications of the findings: Oligomenorrheic adolescents may be reassured for  their chance to have a live birth being comparable with those with a regular menstrual cycle.  Trial registration number: NTR5871